HLA‐G 14 bp deletion/insertion polymorphism and mother‐to‐child transmission of HIV. Issue 3 (March 2014) - Segat, L.; Zupin, L.; Kim, H.‐Y.; Catamo, E.; Thea, D. M.; Kankasa, C.; Aldrovandi, G. M.; Kuhn, L.; Crovella, S.
<x xml:space="preserve">Abstract</x> The human leukocyte antigen HLA‐G, highly expressed at the maternal–fetal interface, has a pivotal role in mediating immune tolerance. In this study we investigated the influence of HLA‐G 14 bp insertion polymorphism in human immunodeficiency virus (HIV)‐1 mother‐to‐child HIV‐1 transmission. The 14 bp insertion polymorphism was analyzed among 99 HIV‐1 positive mothers and 329 infants born to HIV‐positive mothers in Zambia, among whom vertical transmission status and timing had been determined. HLA‐G 14 bp insertion polymorphism was detected using a custom TaqMan single nucleotide polymorphisms (SNPs) genotyping assay. Logistic regression was conducted to examine the associations between HLA‐G alleles and the risk of HIV transmission. The 14 bp insertion allele was more frequent in HIV exposed‐uninfected (EU) infants than in infected infants, and was associated with reduced risk of both in utero (IU) and intrapartum (IP) HIV transmission, after adjusting for maternal cluster of differentiation 4 (CD4) cell count and plasma viral load. Maternal HLA‐G 14 bp insertion genotype and HLA‐G concordance between mother and child were not associated with the risk of perinatal HIV transmission. The presence of the 14 bp insertion associates with protection toward IU and IP HIV infection in children from Zambia, suggesting that HLA‐G could be involved in the vertical transmission of HIV.